2021
DOI: 10.1007/s13752-021-00381-y
|View full text |Cite
|
Sign up to set email alerts
|

The Scapegoat Mechanism in Human Evolution: An Analysis of René Girard’s Hypothesis on the Process of Hominization

Abstract: According to anthropological philosopher René Girard (1923–2015), an important human adaptation is our propensity to victimize or scapegoat. He argued that other traits upon which human sociality depends would have destabilized primate dominance-based social hierarchies, making conspecific conflict a limiting factor in hominin evolution. He surmised that a novel mechanism for inhibiting intragroup conflict must have emerged contemporaneously with our social traits, and speculated that this was the tendency to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 85 publications
0
3
0
1
Order By: Relevance
“…Pendidikan moral, etika, mental, spiritual, dan perilaku positif ditumbuhkan guna membentuk kepribadian siswa, dan para guru serta siswa terlibat secara interaktif dalam proses pendidikan (Apandie & Rahmelia, 2020Fiddler, 2017;Lu & Lu, 2010;Munte, 2022a;Pohl, 2011;Riordan, 2021;Teriasi et al, 2022;van Wynen & Niemandt, 2020;Wainarisi & Tumbol, 2022a;Wersig & Wilson-Smith, 2021). Pendidikan menjadi hal yang penting dalam kehidupan manusia sehingga pada proses belajar mengajar ditekankan untuk dapat fokus pada pembentukan kepribadian peserta didik.…”
Section: Pendahuluanunclassified
“…Pendidikan moral, etika, mental, spiritual, dan perilaku positif ditumbuhkan guna membentuk kepribadian siswa, dan para guru serta siswa terlibat secara interaktif dalam proses pendidikan (Apandie & Rahmelia, 2020Fiddler, 2017;Lu & Lu, 2010;Munte, 2022a;Pohl, 2011;Riordan, 2021;Teriasi et al, 2022;van Wynen & Niemandt, 2020;Wainarisi & Tumbol, 2022a;Wersig & Wilson-Smith, 2021). Pendidikan menjadi hal yang penting dalam kehidupan manusia sehingga pada proses belajar mengajar ditekankan untuk dapat fokus pada pembentukan kepribadian peserta didik.…”
Section: Pendahuluanunclassified
“…The term singles is quite often used by Indonesian people. Although not a standardized word, the term singles is often found both in direct conversation and in cyberspace (Apandie & Rahmelia, 2020Apandie, Rahmelia, Risvan, & Kodun, 2022;Casey, Novick, & Lourenco, 2021;Khanolainen et al, 2023;Morgan, 2023;Riordan, 2021). This term comes from the word jomlo which means old girl which then changes its meaning to jomblo which means someone who does not have a partner.…”
Section: Introductionmentioning
confidence: 99%
“…This, he suggested, was one of the main causes of early hominin conflict, or intragroup conflict at least. His scapegoat hypothesis (Girard, 1986;Riordan, 2021) posits that such conflict would have been countered by a phenomenon which would itself have been an emergent property of imitation, that is, a tendency to respond to crises, including conflict-related crises, by imitating the blaming of an often arbitrarily selected victim, culminating in their expulsion, or more likely, their killing by mob violence. He suggested that such spontaneous, violent and cathartic events had strong unifying, and thus coordinating effects on communities, and were the origin of mythological, religious, and by extension moral, narratives, as archaic communities may have, post hoc, misidentified the victim as God-like, perceiving them to have both caused and resolved the crisis.…”
Section: Introductionmentioning
confidence: 99%